Feasibility study for the collection of wasted vegetable oils in the Canton of Baños De Agua Santa and proposal for the incorporation of a biodiesel production plant as a strategy for sustainable urban development - Luna Radharani Alzate; Mena Alfredo; Setiadi Rukuh (E3S Web of Conferences)
In Ecuador, there is 51.78% of renewable energy from which 1.55% is biomass. The development of technologies regarding Waste-to-Energy is clearly an urge. This study seeks to promote the implementation of this type of technology, in concordance with the SDGs. Baños de Agua Santa, is one of the most visited tourist locations in Latin America and does not have a waste recycling plan. The objective of this project was to evaluate the feasibility of recycling vegetable oil and to provide a solution for the existing environmental problems that would incorporate a biodiesel production plant. Therefore, an informational survey of the amount of oil discarded daily by restaurants was collected and data was evaluated to determine the adequate capacity of a biodiesel plant.In addition, the amount of CO2 that could be reduced if biofuel was incorporated in the same county or in places of ecosystems conservation, like the Galapagos Islands, was calculated. The implementation of a biodiesel production plant would definitely play a significant role in order to promote a sustainable development in the city of Baños de Agua Santa. Cash flow made for 5 years show a NPV of $50,314.89, wish a decrease of1,923,902.16 g of CO2.